Muscle-Derived Lumican Stimulates Bone Formation via Integrin α2β1 and the Downstream ERK Signal - Lee, Jin Young; Park, So Jeong; Kim, Da Ae; Lee, Seung Hun; Koh, Jung-Min; Kim, Beom-Jun (Frontiers in Cell and Developmental Biology, 2020)
Skeletal muscle and bone are highly interrelated, and previous proteomic analyses suggest that lumican is one of muscle-derived factors. To further understand the role of lumican as a myokine affecting adjacent bone metabolism, we investigated the effects of lumican on osteoblast biology. Lumican expression was significantly higher in the cell lysates and conditioned media (CM) of myotubes than those of undifferentiated myoblasts, and the known anabolic effects of myotube CM on osteoblasts were reduced by excluding lumican from the CM. Lumican stimulated preosteoblast viability and differentiation, resulting in increased calvaria bone formation. The expression of osteoblast differentiation markers was consistently increased by lumican. Lumican increased the phosphorylation of ERK, whereas ERK inhibitors completely reversed lumican-mediated stimulation of Runx2 and ALP activities in osteoblasts. Results of a binding ELISA experiment in osteoblasts show that transmembrane integrin α2β1 directly interacted with lumican, and an integrin α2β1 inhibitor attenuated the stimulation of ERK and ALP activities by lumican. Taken together, the results indicate that muscle-derived lumican stimulates bone formation via integrin α2β1 and the downstream ERK signal, indicating that this is a potential therapeutic target for metabolic bone diseases.